Fungal pathogens—a sweet and sour treat for toll-like receptors - Bourgeois, Christelle; Kuchler, Karl (Frontiers in Cellular and Infection Microbiology, 2012)
Hundred-thousands of fungal species are present in our environment, including normal colonizers that constitute part of the human microbiota. The homeostasis of host-fungus interactions encompasses efficient fungal sensing, tolerance at mucosal surfaces, as well as antifungal defenses. Decrease in host immune fitness or increase in fungal burden may favor pathologies, ranging from superficial mucocutaneous diseases to invasive life-threatening fungal infections. Toll-like receptors (TLRs) are essential players in this balance, due to their ability to control both inflammatory and anti-inflammatory processes upon recognition of fungal-specific pathogen-associated molecular patterns (PAMPs). Certain members of the TLR family participate to the initial recognition of fungal PAMPs on the cell surface, as well as inside phagosomes of innate immune cells. Active signaling cascades in phagocytes ultimately enable fungus clearance and the release of cytokines that shape and instruct other innate immune cells and the adaptive immune system. Some TLRs cooperate with other pattern recognition receptors (e.g., C-type lectins, Galectins), thus allowing for a tailored immune response. The spatio-temporal and physiological contributions of individual TLRs in fungal infections remains ill-defined, although in humans, TLR gene polymorphisms have been linked to increased susceptibility to fungal infections. This review focuses entirely on the role of TLRs that control the host susceptibility to environmental fungi (e.g., Aspergillus, Cryptoccocus, Coccidoides), as well as to the most frequent human fungal pathogens represented by the commensal Candida species. The emerging roles of TLRs in modulating host tolerance to fungi, and the strategies that evolved in some of these fungi to evade or use TLR recognition to their advantage will also be discussed, as well as their potential suitability as targets in vaccine therapies.